Religious Education For The Environment: Integrating Eco-Theology in The Curriculum of Islamic Religious and Character Education to Enhance Environmental Education in Indonesia - Rohman, Abdul; Kurniawan, Edi -; Syifauddin, Muhammad -; Muhtamiroh, Siti -; Muthohar, Ahmad - (Nadwa: Jurnal Pendidikan Islam, 2024)
Environmental education (EE) is a crucial issu of amid acute environmental degradation. This study aims to analyze the content of Islamic eco-theology in Indonesia's Islamic Religious and Character Education (IRCE) curriculum and integrate it into the curriculum as a form of offering ethical spirituality in environmental education to enhance environmental education. This study is qualitative research that incorporates the literature study supported by structured interviews and document studies. Interviews were used to collect data that concerned teachers of high schools of IRCE in Semarang, Central Java. Document studies were employed to address the IRCE curriculum of High Schools, journal articles, and government policy documents. Data analysis used the descriptive-interactive method. The results showed that the curriculum of IRCE emphasizes the affective domain in environmental education matters. However, it does not yet address the cognitive one appropriately, so IRCE teachers teach environmental education by inserting relevant IRCE themes. This study emphasizes the importance of integrating eco-theology in the IRCE curriculum and recommends that Islamic eco-theology be included in the IRCE curriculum in Indonesia so that the inculcation of environmental education values can work better through IRCE learning